The Trend of Integrated Reporting in Emerging Markets: A Case Study of Indonesia - Rizki Nur Amelia Bastian; Ika Permatasari (International Journal of Economics and Management Sciences, 2025)
This study analyzes the implementation of Integrated Reporting (IR) in Indonesia based on the International Integrated Reporting Council (IIRC) framework, aiming to evaluate the trends in IR adoption over the past three years and assess the extent to which companies in Indonesia have aligned their reporting practices with IIRC standards. Using content analysis and one-way repeated measures ANOVA, this research examines integrated annual reports of companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period, measuring the quality of IR implementation through a checklist derived from the International Integrated Reporting Framework (IIRF). The findings reveal that IR practices in Indonesia have significantly improved over time, with key dimensions experiencing notable enhancements, including stakeholder relationship, consistency and comparability, operating context, risk, governance, and performance, critical indicators for ensuring transparency and effectiveness in integrated reporting. Furthermore, this study contributes to the development of a matrix or quality checklist for IR, based on a normative interpretation of the IIRF, providing valuable insights into IR implementation in emerging markets, particularly Indonesia, which serves as an interesting case study since previous research has primarily focused on IR adoption in developed regions such as Europe and South Africa. Practically, this study emphasizes the importance for companies to enhance their IR reporting quality by focusing on aspects such as strategic focus and future orientation, connectivity, consistency, reliability, and comparability, thereby ensuring more transparent, accountable, and globally aligned financial and non-financial reporting practices.